2014
DOI: 10.1016/j.psychres.2013.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Using theories of delusion formation to explain abnormal beliefs in Body Dysmorphic Disorder (BDD)

Abstract: Body Dysmorphic Disorder (BDD) is characterised by overvalued or delusional beliefs of 'imagined ugliness'. Delusional beliefs have been explained by a number of cognitive theories, including faulty perceptions, biases in attention, and corruption of semantic memory. Atypical aesthetics may also influence beliefs in BDD. In fourteen BDD patients, compared to controls (n=14), we examined these theories of beliefs in a cognitive test battery consisting of perceptual organisation and visual affect perception task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 42 publications
3
15
0
1
Order By: Relevance
“…Rather, their performance was statistically indistinguishable from that of OCD and psychiatrically healthy control groups. Our results are consistent with earlier studies that found normal performance among BDD patients on tasks that have been previously associated with abnormalities in schizophrenia, (Reese et al, 2011a, b), including a recently published study demonstrating normal CI (Rossell et al, 2014), despite the prevalence of delusional thinking regarding personal appearance in many BDD patients seen in clinical settings (Phillips et al, 2006). One potential implication of these findings is that PO impairment may be somewhat specific to schizophrenia, and perhaps other clearly neurodevelopmental conditions such as autism (Sun et al, 2012) among psychiatric disorders.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Rather, their performance was statistically indistinguishable from that of OCD and psychiatrically healthy control groups. Our results are consistent with earlier studies that found normal performance among BDD patients on tasks that have been previously associated with abnormalities in schizophrenia, (Reese et al, 2011a, b), including a recently published study demonstrating normal CI (Rossell et al, 2014), despite the prevalence of delusional thinking regarding personal appearance in many BDD patients seen in clinical settings (Phillips et al, 2006). One potential implication of these findings is that PO impairment may be somewhat specific to schizophrenia, and perhaps other clearly neurodevelopmental conditions such as autism (Sun et al, 2012) among psychiatric disorders.…”
Section: Discussionsupporting
confidence: 92%
“…CI impairment has also been observed in aging (Roudaia et al, 2011), dyslexia (Simmers and Bex, 2001), and amblyopia (Polat et al, 1997), and can be affected by psychotomimetic drugs that affect occipital lobe functioning (Uhlhaas et al, 2007; White et al, 2013). To our knowledge, only one prior study has investigated CI in BDD (Rossell et al, 2014). This recent study found normal performance; however, they used an older, card-based version of the task with only 15 stimuli and a lengthy exposure duration (30 seconds).…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, the DC ‐ body (e.g., nose ) and DC ‐ negative (e.g., ugly ) conditions were not associated with DCQ scores. These findings are consistent with the BDD literature, in which Emotional Stroop paradigms failed to detect significant group differences in the BDD‐body word condition (Rossell et al, ), but inconsistent with Onden‐Lim et al () who detected a positive association between DC and the attractive stimuli (comprised of facial features and body parts). Moreover, these results are inconsistent with Buhlmann et al () and Toh et al () who detected greater Stroop interference in the BDD group compared to controls on the BDD ‐ negative word condition.…”
Section: Discussionsupporting
confidence: 88%
“…Forty target words and 40 matched neutral words made up the stimuli selected. The chosen words incorporated stimuli from the four published studies that used dot-probe and Emotional Stroop tasks to measure selective attention biases in DC (with a primary focus on BDD psychopathology) and BDD populations (Buhlmann, McNally, Wilhelm, & Florin, 2002;Onden-Lim et al, 2012;Rossell, Labuschagne, Dunai, Kyrios, & Castle, 2014;Toh, Castle, & Rossell, 2017). Additional stimuli were chosen based on common underlying themes related to these words.…”
Section: Dot-probe Taskmentioning
confidence: 99%
“…Recent research regarding cognitive dysfunction related to psychosis emphasizes that delusions are products of cognitive abnormalities (2)(3)(4). For example, the "jumping-toconclusions" hypothesis of delusion formation postulates that people prone to delusion reach premature conclusions before finding sufficient grounds for that conclusion (4).…”
Section: Introductionmentioning
confidence: 99%